La izquierda se acerca a los uruguayos y los uruguayos se acercan a la izquierda - Jorge Lanzaro (Cahiers des Amériques Latines)
Througout the last decades, the Uruguayan left – gathered in the Frente Amplio – has achieved a notable electoral ascent and in the 2004 elections has good chances to reach the government. This article proposes an explanation of this process, based on the development of the FA as a catch-all party, its structure as a coalition-party and a two-pronged strategy, which combines opposition vis-à-vis the traditional parties, with trends towards ideological moderation and the competition for the center. Prospectively, the article analyses the scenario of an eventual debut in government. These events take place whithin the framework of the Latinamerican liberal transition and as a part of the transformation of one of the most ancient party systems of the world, which preserves its high degree of institutionalization and competitiveness, drawing a expérience which can be compared to those of Brazil or Chile.